2020
DOI: 10.1016/j.omtm.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Methods Matter: Standard Production Platforms for Recombinant AAV Produce Chemically and Functionally Distinct Vectors

Abstract: Different approaches are used in the production of recombinant adeno-associated virus (rAAV). The two leading approaches are transiently transfected human HEK293 cells and live baculovirus infection of Spodoptera frugiperda ( Sf9 ) insect cells. Unexplained differences in vector performance have been seen clinically and preclinically. Thus, we performed a controlled comparative production analysis varying only the host cell species but maintaining all other paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 70 publications
2
98
1
Order By: Relevance
“…Since the baculovirus provides helper function, 208 a single BEV system in conjunction with Sf9 cell lines that stably express rep , can be employed for flexible and high-titer large-scale vector production. 209 Interestingly, a report that vectors produced from Sf9 cells are differentially posttranslationally modified, as compared to those generated from human- or mammalian-derived cell lines raised question as to whether differences in production schemes may impact tropism and transduction efficacies, 210 although further work in this area is necessary to cross-validate these findings. Nonetheless, BEV/Sf9 systems exhibit reduced encapsidation of contaminating DNAs 205 and therefore remain an attractive production strategy for large-scale, clinical-grade vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the baculovirus provides helper function, 208 a single BEV system in conjunction with Sf9 cell lines that stably express rep , can be employed for flexible and high-titer large-scale vector production. 209 Interestingly, a report that vectors produced from Sf9 cells are differentially posttranslationally modified, as compared to those generated from human- or mammalian-derived cell lines raised question as to whether differences in production schemes may impact tropism and transduction efficacies, 210 although further work in this area is necessary to cross-validate these findings. Nonetheless, BEV/Sf9 systems exhibit reduced encapsidation of contaminating DNAs 205 and therefore remain an attractive production strategy for large-scale, clinical-grade vectors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that the rAAV capsid PTMs and rAAV genome methylation differ between two main platforms corresponding to the plasmid-transfected human HEK293 cells and the BEV-infected insect Sf9 cells. It also showed that rAAVs derived from the HEK293 cells are more potent than rAAVs derived from Sf9 cells [54]. However, this study only focused on rAAV1 and rAAV8, and did not illustrate the relevance between these differences and the activity of rAAVs.…”
Section: Discussionmentioning
confidence: 94%
“…The second question is related to the efficiency of vector genome packaging in insect cells. In general, insect cells have been reported to produce more AAV empty capsids [43,56,93] compared to mammalian cell platforms, [94][95][96] which counteracts any success achieved with genomic and functional particles of wtAAV in the presence of helper virus functions. [97] Moreover, in contrast to well-defined and wellcharacterized helper genes of adenovirus or HSV, [98,99] the baculovirus helper elements have not yet been fully identified, even though their helper function has been known for almost two decades.…”
Section: Insect Cell and Baculovirus Engineeringmentioning
confidence: 99%
“…The second question is related to the efficiency of vector genome packaging in insect cells. In general, insect cells have been reported to produce more AAV empty capsids [ 43,56,93 ] compared to mammalian cell platforms, [ 94–96 ] which counteracts any success achieved with increased cell‐specific AAV yield and necessitates active efforts towards engineering insect cells or BEVs to improve packaging efficiency and produce more functional particles. A head‐to‐head comparison of the mammalian cell versus insect cells for wild type AAV production may help identify any insect‐cell specific limitations for producing packaged AAV particles because mammalian cells, the natural host of AAV, have been reported to produce nearly 100% genomic and functional particles of wtAAV in the presence of helper virus functions.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation